Improving Children's Gross Motoric Through Rhythmics In Class B-1 At Al-Muchlisin Batuang Kindergarten Bajawek Sub-District Koto Parik Gadang Diateh Solok Selatan District - Jeni Afrianti; Yesni Yenti; Rezi Susanto; Nurhamidah Nst (Educare: Journal Educational and Multimedia, 2023)
This research is motivated by the problems that researchers found in Class B-1 TK Al-Muchlisin Batuang Bajawek. When making observations, it was found that there were problems, namely the children's learning outcomes about rhythmic gymnastics were not as expected. This study uses a classroom action research methodology, namely to improve the constraints faced by teachers during learning activities. In practice, the researcher will collaborate with the teacher who acts as observer 1 and colleagues as observer 2. This activity is carried out with 10 students of class B-1 with 2 meetings for each cycle. The results of the study after being given action using the Rhythmic Gymnastics model in cycle I and cycle II showed an increase. Increasing children's creativity in the initial conditions in rhythmic gymnastics activities that scored BSH + BSB indicators of imitating movements according to the child's imagination, cycle I by 30% increased in cycle II to 80%, indicators demonstrating animal movements accompanied by music cycle I by 20 % increased in cycle II to 90%, the indicator of doing animal movement exercises from start to finish without the help of the teacher cycle I by 10% increased in cycle II to 80%. This proves that Rhythmic Gymnastics can improve student learning outcomes in Class B-1 TK Al-Muchlisin. the indicator of doing animal movement exercises from start to finish without the help of the teacher cycle I by 10% increased in cycle II to 80%. This proves that Rhythmic Gymnastics can improve student learning outcomes in Class B-1 TK Al-Muchlisin. the indicator of doing animal movement exercises from start to finish without the help of the teacher cycle I by 10% increased in cycle II to 80%. This proves that Rhythmic Gymnastics can improve student learning outcomes in Class B-1 TK Al-Muchlisin.